Risk-assessment algorithm and recommendations for venous thromboembolism prophylaxis in medical patients - Rocha, Ana T.; Paiva, Edison F.; Lichtenstein, Arnaldo; Milani Jr., Rodolfo; Cavalheiro-Filho, Cyrillo; Maffei, Francisco Humberto de Abreu [UNESP] (My University, 2007)
The risk for venous thromboembolism (VTE) in medical patients is high, but risk assessment is rarely performed because there is not yet a good method to identify candidates for prophylaxis. Purpose: To perform a systematic review about VTE risk factors (RFs) in hospitalized medical patients and generate recommendations (RECs) for prophylaxis that can be implemented into practice. Data sources: A multidisciplinary group of experts from 12 Brazilian Medical Societies searched MEDLINE, Cochrane, and LILACS. Study selection: Two experts independently classified the evidence for each RF by its scientific quality in a standardized manner. A risk-assessment algorithm was created based on the results of the review. Data synthesis: Several VTE RFs have enough evidence to support RECs for prophylaxis in hospitalized medical patients (eg, increasing age, heart failure, and stroke). Other factors are considered adjuncts of risk (eg, varices, obesity, and infections). According to the algorithm, hospitalized medical patients ≥40 years-old with decreased mobility, and ≥1 RFs should receive chemoprophylaxis with heparin, provided they don't have contraindications. High prophylactic doses of unfractionated heparin or low-molecular-weight-heparin must be administered and maintained for 6-14 days. Conclusions: A multidisciplinary group generated evidence-based RECs and an easy-to-use algorithm to facilitate VTE prophylaxis in medical patients. © 2007 Rocha et al, publisher and licensee Dove Medical Press Ltd.
Keywords: Embolism and thrombosis; Guideline; Heparin; Prevention and control; Risk factors; Risk-assessment; antineoplastic agent; dalteparin; enoxaparin; estrogen; fondaparinux; gestagen; heparin; hormone; low molecular weight heparin; nadroparin; placebo; recombinant erythropoietin; tamoxifen; thalidomide; warfarin; acute heart infarction; age distribution; cancer; cancer chemotherapy; cancer hormone therapy; central venous catheterization; cerebrovascular accident; clinical protocol; clinical trial; compression therapy; congestive heart failure; deep vein thrombosis; drug dosage form comparison; drug dose comparison; drug efficacy; drug megadose; enteritis; evidence based medicine; hormonal contraception; hormone substitution; hospital patient; human; hyperhomocysteinemia; immobilization; infection; ischemic heart disease; low drug dose; lung embolism; nephrotic syndrome; obesity; paresis; peripheral vascular disease; pregnancy; puerperium; respiratory tract disease; review; rheumatic disease; rheumatoid arthritis; risk assessment; risk factor; Swan Ganz catheter; systematic review; systemic lupus erythematosus; thrombophilia; thrombophlebitis; thrombosis prevention; venous thromboembolism; Algorithms; Humans; Risk Assessment; Thromboembolism